The Presence of an ESBL-Encoding Plasmid Reported During a Klebsiella pneumoniae Nosocomial Outbreak in the United Kingdom - Stephen Mark Edward Fordham; Anna Mantzouratou; Elizabeth Sheridan (Microbiology Research)
An EBSL-encoding plasmid, pESBL-PH, was identified during a nosocomial outbreak of Klebsiella pneumoniae ST628 at a United Kingdom general district hospital in 2018. The plasmid from the earliest 2018 K. pneumoniae strain discovered during the outbreak was assembled using both Oxford nanopore long reads and illumina short reads, yielding a fully closed plasmid, pESBL-PH-2018. pESBL-PH-2018 was queried against the complete NCBI RefSeq Plasmid Database, comprising 93,823 plasmids, which was downloaded on 16 July 2024. To identify structurally similar plasmids, strict thresholds were applied, including a mash similarity ≥0.98. This returned 61 plasmids belonging to 13 unique sequence types (STs) hosts. The plasmids were detected from 13 unique countries, dating from 2012 to 2023. The AMR region of the plasmids varied. Interestingly IS26-mediated tandem amplification of resistance genes, including the ESBL gene blaCTX-M-15 was identified in two independent strains, raising their copy number to three. Furthermore, the genomic background of strains carrying a pESBL-PH-2018-like plasmid were analyzed, revealing truncation of the chromosomal ompK36 porin gene and carbapenem resistance gene carriage on accessory plasmids in 17.85% and 26.78% of strains with a complete chromosome available. This analysis reveals the widespread dissemination of an ESBL-encoding plasmid in a background of resistance-encoding strains, requiring active surveillance.